Efikasi Diri Guru dalam Mengelola Kelas Inklusif: Tantangan dan Harapan Untuk Children Well-being PAUD Berkebutuhan Khusus - Yunengsih Nurul Hidayah; Taopik Rahman; Ribson Siantur (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to analyze teacher self-efficacy in managing inclusive classrooms, focusing on teachers' beliefs in their ability to maintain the well-being of early childhood children with special needs. The research method employed is a literature review, analyzing 15 relevant scientific journal articles. The findings indicate that self-efficacy is a key predictor of successful classroom management and instructional interaction. Teachers with high self-efficacy are capable of transforming operational challenges into humanistic pedagogical strategies, supported by stable emotional regulation skills. The conclusion emphasizes that the well-being of children with special needs in early childhood education settings heavily depends on collaborative synergy among educators and the strengthening of teachers' internal beliefs. Enhancing literacy regarding Individualized Education Programs (IEP) and institutional support are determining factors in realizing socially just inclusive education